Cerebral edema in children with diabetic ketoacidosis: vasogenic rather than cellular?. Issue 4 (June 2014) - Tasker, Robert C; Acerini, Carlo L
<x xml:space="preserve">Abstract</x> Cerebral edema (CE) is accumulation of water in the intracellular or extracellular spaces of the brain. Vasogenic edema occurs when there is breakdown of the tight endothelial junctions of the blood–brain barrier (BBB), leading to extravasation of intravascular protein and fluid into the interstitial space of the brain. In cellular edema the BBB remains intact and there is swelling of astrocytes with corresponding reduction in extracellular space. In this review we bring together clinical evidence from neuropathology and cerebral magnetic resonance (MR) studies in pediatric patients presenting in diabetic ketoacidosis (DKA), and use applied physiology to understand whether CE complicating DKA is vasogenic, rather than cellular in origin. Because the first‐line of defense against CE is the interface between the intravascular compartment and the extracellular space in the brain much of the focus in this review is the BBB. The principal pathologic finding in fatal cases is perivascular with BBB disruption and albumin extravasation, suggesting increased vascular permeability. DKA induces an inflammatory response and the mechanism of BBB transcellular permeability may be an immunologic cascade that disrupts tight junctions. The principal MR finding in subclinical cases of CE is vasogenic rather than cellular edema. We propose that the following physiology be considered when treating cases: bolus dose of intravenous mannitol may result in fall in serum sodium concentration, and therefore clinical worsening. Failure to respond to mannitol should prompt the use of 3% hypertonic saline (HS). Bolus dose of intravenous 3% HS is expected to effect vasogenic edema provided that the reflection coefficient is close to 1. Failure to respond to 3% HS should prompt the use of mannitol.